Biochar from sugarcane apexes in the initial growth of cucumber - Juárez-López, Porfirio; Pérez-Cabrera, Carlos Alberto; Anzaldo-Hernández, José; Alia-Tejacal, Irán; Salcedo-Pérez, Eduardo; López-Martínez, Víctor (Revista Mexicana de Ciencias Agrícolas, 2025)
One of the main uses of biochar is as a soil improver; however, there are few studies on its use as a substrate with the aim of reducing the use of commercial peat moss. The effect of the physical properties of biochar from sugarcane apexes on the growth of ‘Thunderbird’ cucumber seedlings was evaluated. The treatments were mixtures of Bsca and peat moss (P): 0/100, 20/80, 40/60, 60/40, 80/20, and 100/0 v/v. The sowing was carried out in a greenhouse of the Autonomous University of the State of Morelos and physical properties of the substrates and growth variables in cucumber seedlings were evaluated with a completely randomized experimental design and randomized blocks, respectively. Peat moss produced the highest seedling growth; on the other hand, the proportions 20Bsca:80P and 40Bsca:60P allowed a good root development by presenting a fresh root weight, with 607.83 and 664.83 mg; whereas in root dry weight, they had 39.83 and 37.33 mg, respectively, values similar to those obtained in peat, these results were related to the physical properties of these mixtures, where the particle size determined the pore space available for water and air. Biochar from sugarcane apexes can be added up to 40% to commercial peat moss without altering the physical properties of an ideal substrate; likewise, mixtures of 20 and 40% biochar with peat moss allow the growth of cucumber seedling roots similar to those obtained in commercial peat moss.